Primary hydatid cyst of thigh: a rare case report - Sonam Agrawal; Dr. Prateek Sharda; Gaurav Gupta; Sangeeta Gupta; Ashikesh Kundal (Pediatric Review: International Journal of Pediatric Research, 2020)
Primary hydatid cyst elsewhere in the body is rare, as these cysts are always secondary to a hydatid of the liver or lungs. We report a case of 14-year-old girl presented with a swelling on medial aspect of left upper thigh which was gradually increasing in size since last 12 months. Ultrasonography diagnosed it as hydatid cyst, there was no swelling in the liver, lungs or elsewhere in the body, CT scan further reinforced the diagnosis. The swelling was removed en bloc and albendazole was given.